Ultrasound Elastography-A Useful Tool in Assessment of Diffuse Liver Disease - John, Praveen Kumar; K, Chaithra T; M, Chidananda Murthy; Monteiro, Francis N. P. (Asian Journal of Medical Radiological Research, 2019)
Background: Diffuse liver diseases are commonly encountered in clinical practice and on radiological imaging .Early detection and accurate diagnosis are extremely important in the definitive management of such patients. Ultrasonography is the widely used and the first line of radiological investigation in patients suspected with diffuse liver disease. Ultrasound elastography is a recent advance in the field of ultrasonography which has reportedly improved the accuracy in the assessment of severity of liver fibrosis in diffuse liver diseases. Objectives: 1.To evaluate the role of elastography for evaluation of diffuse liver disease. 2. To evaluate the sensitivity and specificity of sonoelastography in detection and characterisation of diffuse liver disease and correlation with other clinical diagnostic modalities and histopathology as gold standard. Subjects and Methods: Study was conducted from from August 2014 to August 2016.Based on inclusion and exclusion criteria, 30 cases of diffuse liver diseases were included in the study.The ultrasound and ultrasound elastography were done in the AJ Institute of Medical Sciences. These 30 cases were subjected to FNAC/Tru-cut Biopsy for the confirmation of ultrasound and ultrasound elastography finding and establishment of final diagnosis. Results: In our study of 30 cases of diffuse liver lesions ,after Metavir scoring 13% were F1,16% were F2, 23% were F3,and 46% were F4.The sensitivity and specificity for F1 and F2 were 100% and 100%, for F3 was 71% and 91%, for F4 85 and 87%.the mean cut off value for the cirrhosis was found to be 18kPa. Conclusion: Ultrasound elastography is a recent advance in the field of ultrasound, which is a non invasive method in assessment of severity of liver fibrosis and end stage cirrhosis.